Anti-Americanism in Europe : a Cultural Problem. - Berman, Russell A. (Hoover Institution Press, 2010)
In his analysis of Europe's ambivalence toward jihadist terror and the spread of aggressive Islamism, with particular emphasis on the European responses?or lack thereof?to this violent anti-modernism, Russell A. Berman describes how some European countries opt for appeasement and apologetics, whereas others muster the strength to defend their way of life and stand up for freedom. He describes a complex continent of different nations and traditions to further our understanding of the range of reactions to Islamism.